Acquisition of motor skills - Abernethy, B. (Better Coaching, 1991)
The concepts presented should govern the structure of skill-development experiences at sport practices. The experiences and dynamics of skills practice differ between sports. The nature of the competitive situation will usually dictate the scope and variations of activities that have to be learned and trained. However, in all sports there is a limitation on the extent of beneficial activities which will affect competitive performances positively.